Middle latency cutaneous reflexes in intrinsic human hand muscles are modulated in badminton players - Komiyama, T.; Tatematsu, M.; Nakajima, T.; Sakamoto, M.; Tazoe, T.; Omori, S. (Advances in Exercise and Sports Physiology, 2008)
The long latency (50ms) cutaneous reflex was thought to be mediated via transcortical pathways and has been demonstrated to be subject to plastic change while performing a novel task or by motor learning.We hypothesized that the long latency cutaneous reflexes were modulated in skillful badmintonplayers who continue skilful physical training, in particular training of the forearm and hand muscles.Therefore, we compared the organization of long latency cutaneous reflexes in intrinsic hand muscles (first dorsal interosseous muscle; FDI, abductor pollicis brevis; APB and abductor digiti minimi; ADM) following non-noxious electrical stimulation to the digits of the hand (digit1;D1,digit2; D2 and digi t5; D5) between control subjects and badminton players. Cutaneous reflexes were elicited while the subjects performed isolated isometric contraction of the APB(D1abduction), FDI (D2 abduction) and ADM (D5 abduction) muscles.It was found that the magnitude of the excitatory response (latency~60 ms,E2) in the FDI and APBis significantly larger in normal subjects than in badminton players when the stimulation was applied to anagonist or nearby digit. However, themagnitude of E2 for all muscles was inversely significantly larger in badminton players than in normal subjects when the stimulation was applied to the distal digit. Also, the magnitude of E2 in the APB following D1 stimulation was larger in the right than the left side.These findings suggest that plastic changes in E2 occurred in badminton players to cope with the neural and biomechanical constraints for gripping and swinging a badminton racket.